Kajian Fasilitas Equipment Parking Area Guna Kelancaran Operasional Kendaraan di Make Up dan Break Down Area Bandara I Gusti Ngurah Rai Bali - Thrifty Harianja; Elfi Amir; Dian Anggraini Purwaningtyas (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
I Gusti Ngurah Rai International Airport – Bali is one of the airports with the busiest flight traffic in Indonesia, for both domestic and international routes. The high intensity of operational activities on the airside demands optimal management of all supporting elements, one of which is Ground Support Equipment (GSE). GSE plays a vital role in supporting aircraft movements and handling baggage, cargo, and passengers. Therefore, the provision of well-organized Equipment Parking Area (EPA) facilities in the Make Up and Break Down areas is crucial to ensure smooth and safe operations on the apron. This paper aims to examine the effectiveness of EPA provision and management in supporting GSE work efficiency, while identifying challenges and providing solutions to various emerging problems. The method used is a descriptive qualitative approach through direct observation, field documentation, and analysis of the actual layout compared to the provisions of the Directorate General of Civil Aviation Regulation No. PR 21 of 2023 concerning Technical and Operational Standards for Civil Aviation Safety Regulations. This research also complements EPA management practices at other airports in Indonesia, to provide a constructive comparative perspective. The study results indicate that the current management of the EPA at I Gusti Ngurah Rai Airport is not optimal. The main problems identified include irregular parking of GSE vehicles, the absence of zoning based on vehicle type, minimal markings, and a weak monitoring system due to limited personnel. As a result, congestion often occurs on GSE operational routes, which can disrupt the smooth operation of ground handling services. Based on these findings, proposed improvements include redesigning the EPA layout based on vehicle classification, installing signs and vehicle flow maps in strategic areas, and implementing an integrated technology-based monitoring system such as CCTV and digital access control.